GENDER REPRESENTATION OF CHIMAMANDA NGOZI ADICHIE IN ‘WE SHOULD ALL BE FEMINISTS’ - Feny Anggeria (Department of Master of Linguistic, Universitas Airlangga, 2019)
Gender is the study of women and men among their roles in society. Since the year of emancipation occurs in all the country, the term gender becomes popular. Talking about gender, of course, is same as talking about feminism. Chimamanda Ngozi Adichie is one of the most influential woman in Africa. Her speech and essay, ‘We Should All Be Feminists’, which serves the idea of feminism have changed the term feminism with a high balance discussion. The study of gender, in Africa, has too often taboo because there is no equality insight between women and men. By implementing the transitivity in Halliday’s SFL (Systemic Functional Linguistics), it is necessary to know the language used by Chimamanda Ngozi Adichie. The type of the data in this research is quantitative and qualitative data. This study also uses Critical Discourse Analysis as the approach. Hence, the library research supports the understanding of the material which is applicable and accurate to obtain the source of the data.